GASTROPROTECTIVE EFFECTS OF LEEJUNG-TANG, AN ORIENTAL TRADITIONAL HERBAL FORMULA, ON ETHANOL-INDUCED ACUTE GASTRIC INJURY IN RATS - Shin, In-Sik; Lee, Mee-Young; Lim, Hye-Sun; Seo, Chang-Seob; Ha, Hye-Kyung; Shin, Hyeun-Kyoo (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Leejung-tang (LJT, Rechu-to in Japanese and Lizhong-tang in Chinese) is an oriental traditional traditional herbal formula. LJT has been used for treatment of gastrointestinal disorders in Korea, Japan, and China for a long time. In present study, we investigated the protective effects of LJT against absolute ethanol induced gastric injuries. Rats in the control group were given PBS orally (5 mL/kg body weight) as the vehicle, and the absolute-ethanol group (EtOH group) received absolute ethanol (5 mL/kg body weight) by oral gavage. Rats in the positive control group were given omeprazole orally (50 mg/kg body weight) 2 h prior to the administration of absolute ethanol. The treatment groups received LJT (400 mg/kg body weight) 2 h prior to absolute ethanol administration. All rats were sacrificed 1 h after receiving the ethanol treatment. The stomach was excised for macroscopic examination and biochemical analysis. The administration of LJT protected gastric mucosa against ethanol-induced acute gastric injury, including hemorrhage and hyperemia. LJT reduced the increase in lipid peroxidation in ethanol-induced acute gastric lesions. LJT increased GSH content and activities of the antioxidant enzymes, catalase, glutathione-S-transferase, glutathione reductase, glutathione peroxidase, and superoxide dismutase. These results indicate that LJT protects gastric mucosa against ethanol-induced acute gastric injury by increasing their antioxidant content. We suggest that LJT can be developed as an effective drug for the treatment of acute gastric injury.